Managing colleges and universities : issues for leadership - Hoffman, Allan M. (Allan Michael); Summers, Randal W., 1946- (Bergin & Garvey, 2000)
Annotation Higher education is facing up to new challenges, and Hoffman and Summers show what these are and how schools are coping. The rise of "for-profit education," shrinking budgets and enrollment challenges, technological advances in education methodology, the graying of the higher education workforce, and increasing minority and adult enrollment are just some of the challenges discussed